(untitled) (AYUSHDHARA, 2016)
Ayurveda being evidence based science mentioned Samprapti vighatana as a mode of treatment which can be applied in so many diseases evolving in this era. Avascular necrosis (AVN) is one of the rare, progressive disease conditions of the bone which require a life time management. It affects the bones of the joints particularly at their ends. Here death of the bone tissue occurs due to lack of blood supply. It is mainly idiopathic in nature and some of the causes that may lead to AVN are long term use of steroids, excess intake of alcohol and some autoimmune disease. Long term use of steroids and joint replacement are the only way of management in modern medical science. This gives scope to find other alternative treatment measures to rescue the patients from harmful erects of steroids. In Ayurveda AVN can be compared to that of Maragavarodha janyasandhivata, a disease manifesting due to Srotodushti of Asthidhatu caused by Vatavriddhi. The objectives of the treatment include preservation of the structure and symptomatic relief. The treatment opted/suggested in this condition in Ayurveda includes Srotoshodhana thereby increasing the vascularity as well as nutritional supplementation to Asthi Dhatu. The present study has been conducted on a patient suffering from AVN of the Hip joint since 2 years which is idiopathic in origin. The treatment plan includes Abhyanga followed by Patraptali pindasweda, followed by Guduchyadi yaapanavasti for 14 days. The drugs of the Guduchyadi yaapanavasti are known to the effective in clearing channels as well as in alleviating Vata. Patient got marked relied from pain, tenderness and gait is improved. The pathogenesis, mode of action of the treatment, results are discussed in detail in full paper.